2019
DOI: 10.3390/ijms20030702
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Silencing Attenuates Multiple Myeloma Cell Adhesion to Bone Marrow Stromal Cells

Abstract: The bone marrow (BM) microenvironment plays an important role in supporting proliferation, survival and drug resistance of Multiple Myeloma (MM) cells. MM cells adhere to bone marrow stromal cells leading to the activation of tumour-promoting signaling pathways. Activation of the NFκB pathway, in particular, is central to the pathogenesis of MM. Tumour necrosis factor receptor-associated factor 6 (TRAF6) is a key mediator of NFκB activation and has previously been highlighted as a potential therapeutic target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…NF-κB is an inactive heterodimer composed of p50 and p65 subunits interacting with a member of the inhibitory IκB family in resting cells (Bai et al, 2016). Upon stimulation by activating signals, the IKK complex phosphorylates IκBα, promoting its degradation and freeing NFκB p50/p65 to translocate to the nucleus and initiate transcription (Wang et al, 2017; Morgan et al, 2019). In our study, mTOR deficiency suppressed NF-κB activation followed by decreased levels of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is an inactive heterodimer composed of p50 and p65 subunits interacting with a member of the inhibitory IκB family in resting cells (Bai et al, 2016). Upon stimulation by activating signals, the IKK complex phosphorylates IκBα, promoting its degradation and freeing NFκB p50/p65 to translocate to the nucleus and initiate transcription (Wang et al, 2017; Morgan et al, 2019). In our study, mTOR deficiency suppressed NF-κB activation followed by decreased levels of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TRAF6 has become a potential therapeutic target for multiple tumors, such as multiple myeloma, liver cancer, and melanoma [42][43][44]. The adhesion of multiple myeloma cells to bone marrow stromal cells leads to activation of tumor-promoting signaling pathways, while TRAF6 promotes adhesion through NF-κBinduced adhesion factors [45]. Although previous study showed that TRAF6 does not affect NF-κB pathway in cancer cells under normal condition [46], Zhu et al found that TRAF6 promotes colorectal cancer cells (SW48 and HCT116) proliferation and migration through NF-κB nuclear translocation [47].…”
Section: Traf6 and Nf-κb Pathwaymentioning
confidence: 99%
“…Fang J. et al [9] showed that the absence of Traf6 reduces the self-renewal ability of hematopoietic stem cells, and results in premature death and hematological defects. A recent study [23] reported that activating the NFκB pathway is the key to the pathogenesis of MM and TRAF6 has been previously found to act as an important mediator in NFκB activation. Through rescue experiments, we discovered that the effect of TRAF6 on cells was opposite to that of miR-361-3p on the MM cells.…”
Section: Discussionmentioning
confidence: 99%